1999
DOI: 10.4269/ajtmh.1999.60.458
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Burkholderia pseudomallei in Thailand.

Abstract: Abstract. The distribution of Burkholderia pseudomallei in soil collected from four regions of Thailand and the frequency of B. pseudomallei infections in patients attending government hospitals throughout Thailand in 1997 were surveyed. A total of 3,585 soil samples collected from 896 sites in four regions of Thailand were cultured for B. pseudomallei using selective enrichment broth and modified Ashdown's agar. The organism was recovered in 4. 4%, 6.1%, 20.4%, and 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 14 publications
2
52
0
Order By: Relevance
“…B. pseudomallei isolates were tested for arabinose assimilation by growth on minimal salts agar containing 0.2% L-arabinose (Wuthiekanun et al 1996) ( Lertpatanasuwan et al 1999), all isolates causing melioidosis in our study were Ara-. Our findings support previous observations described by Vuddhakul et al (1999) in Thailand and by Miralles et al (2004) in Brazil. In this study, the results of the biochemical profile in the OF medium tests with lactose, maltose, and mannitol for isolates 1 and 3 differed from those Gilligan and Whittier (1999), but this may reflect differences in methodology utilized for assimilation tests, rather than genuine differences in Brazilian isolates.…”
supporting
confidence: 93%
“…B. pseudomallei isolates were tested for arabinose assimilation by growth on minimal salts agar containing 0.2% L-arabinose (Wuthiekanun et al 1996) ( Lertpatanasuwan et al 1999), all isolates causing melioidosis in our study were Ara-. Our findings support previous observations described by Vuddhakul et al (1999) in Thailand and by Miralles et al (2004) in Brazil. In this study, the results of the biochemical profile in the OF medium tests with lactose, maltose, and mannitol for isolates 1 and 3 differed from those Gilligan and Whittier (1999), but this may reflect differences in methodology utilized for assimilation tests, rather than genuine differences in Brazilian isolates.…”
supporting
confidence: 93%
“…A recent study also reported a higher incidence of B. pseudomallei in soil and water samples in northeastern Thailand, and that the distribution of B. pseudomallei was uneven even in positive sites. 22 Since isolations in the later study were entirely by cultural methods rather than animal inoculation as in our study, the more recent samplings could have included a higher proportion of the avirulent species (B. thailandensis). 21 Although the higher reported incidence of cases in the northeast region of Thailand argues against this hypothesis, the matter is now being further studied.…”
Section: Discussionmentioning
confidence: 93%
“…21 Although the higher reported incidence of cases in the northeast region of Thailand argues against this hypothesis, the matter is now being further studied. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Melioidosis patients are infected either by inhalation or percutaneous inoculation from contaminated muddy soil or stagnant water in endemic locations and have resulted in pneumonia and/or sepsis with high mortality rate (up to 40%) of treated patients (Cheng and Currie, 2005;White, 2003;Dance, 1991). In Thailand, the highest incidence of melioidosis cases has been seen in the northeast with the highest presence of B. pseudomallei in soil (Vuddhakul et al, 1999). A prospective cohort study in northeast Thailand during 1997 to 2006 revealed the increasing incidence of human melioidosis indicating that the disease is an emerging public health issue (Limmathurotsakul et al, 2010).…”
Section: Introductionmentioning
confidence: 99%